Relationship between IC50determined in vitro/in vivoand the fungicide rate used in the Field - Reis,Erlei Melo (2015)
Published data containing fungicide concentrations that control 50% (IC50) of a given fungus were analyzed. In the analysis we considered: (i) the IC50 determined in vitroand in vivofor a given fungicide and for a specific fungus; (ii) the concentration (g/ha) of active ingredient for the fungicide indicated to control a specific disease in the field; (iii) water volume of 120/L used in the spray; (iv) the fungicide a.i. concentration (mg/L) in 120 L volume; (v) and the ratio of the concentration used in the field with that determined in the laboratory. The analysis were performed by using IC50 data for DMIs, QoIs, a carbamate and a benzimidazol against the following fungi Bipolaris sorokiniana, Drechslera tritici-repentis, D. siccans, Fusarium graminearum, Puccinia triticina, Exserohilum turcicum, Phakopsora pachyrhiziand Corynespora cassiicola. The fungicide concentrations sprayed in the field were 33.9 (D. siccansand trifloxystrobin) to 500,000.0 (E. turcicumand iprodione) times higher than that determined in the laboratory. It was concluded that the IC50 was not related to the concentration used in the field and therefore should be used to compare the power among fungicides and to monitor the fungal sensitivity shift towards fungicides